Challenges and problems of agricultural land use changes in Lithuania according to territorial planning documents: Case of Vilnius district municipality. (June 2022) - Edita, Abalikstiene; Dalia, Perkumiene
Abstract: Land use is the result of direct or indirect decisions to change the current use of land at the level of individual landowners, regional or national authorities, international organizations, or any other land-related interests. Territorial planning is one of the tools for controlling urbanization processes in rural areas. The aim of this article is to analyze the territorial planning documents regulating agricultural land use change in Vilnius district municipality (Lithuania) and to assess the impact of land change and use on it. Until now, land use changes often remain only in the form of statistical indicators, territorial planning document solutions are presented without an abstract assessment of what would happen if all the planned changes in territories do occur, there are not enough legal safeguards in territorial planning, despite the widely accepted assumption that planning affects land use changes. In order to better analyze the role of territorial planning in land use change in the Republic of Lithuania, it is appropriate to evaluate: 1) the legal regulation of territorial planning documents in terms of land use change; 2) measures for the implementation of territorial planning documents through management processes and 3) the influence of various factors for the implementation of decision-making. One of the most common problems is that quite often agricultural land use changes challenges are solved without considering the many human activities in the environment. That is why territorial planning documents are being prepared, which provide the main criteria for how to organize a territory. Another problem that arises in this area is that agricultural land use change processes have intensified with the restoration of independence and the substantial contribution of private capital to urban development.